Evaluasi Kualitas Batubara dari Front Penambangan Hingga Stockpile di Pit 1 Banko Barat PT Bukit Asam Tbk Tanjung Enim - Inda Pratama Putri; Janiar Pitulima; Mardiah Mardiah (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2019)
Mining Pit 1 Banko Barat in Bukit Asam is a mining location that used open pit system of mining. Coal quality is an important part of the mining industry, because it's related directly to coal marketing. Coal sampling test process which determine quality prove that quality in front mining and stockpile is decreasing from recent month with 4903 Kcal/kg. The decreasing in quality will also result in price reduction. Based on that condition, evaluation of coal sampling quality test result needs to be done to discover the cause of quality decreasing, so that various efforts can be made to increase quality to match the price standard. Research method using proximate and ultimate analysis for coal quality. There are 20 coal samples used in the front, 24 samples in stockpile and 8 samples in temporary stockpile. Coal quality in front mining has 28.24% total moisture, 13.8% inherent moisture, 2.11% ash content, 33.81% volatile matter, 35.98% fixed carbon, 0.42% total sulphur and 4,987.5 kcal/kg. Coal quality in stockpile has 28.35% total moisture, 14.26% inherent moisture, 3.73% ash content, 33.87% volatile matter, 34.09% fixed carbon, 0.41% total sulphur and 4,908.5 kcal/kg. Irrelevance factor is caused by water puddle, mining process, coal cumulation that stays too long in temporary stockpile and spontaneous combustion. Efforts that can be done to handle irregularities are drainage system and pump additions, mining process optimization, FIFO management system implementation and spontaneous combustion handling.